The information needs of women diagnosed with Polycystic Ovarian Syndrome - implications for treatment and health outcomes - Braunack-Mayer Annette J; Avery Jodie C (BMC, 2007)
Abstract Background This paper reports the findings of an exploratory study about the information women diagnosed with Polycystic Ovarian Syndrome (PCOS) want to know about their condition and the consequences of this information for future treatment and health outcomes. Methods In-depth qualitative interviews regarding their information needs were undertaken with ten South Australian women diagnosed with PCOS. These women were aged 28-38 years and at differing stages of their fertility experience. The time since diagnosis ranged from 1-17 years. The main outcome measures sought were the identification of the information needs of women diagnosed with Polycystic Ovarian Syndrome (PCOS) during different periods of their lives; how and where they obtain this information, and the consequences of this information for future treatment and health outcomes. Results The women with PCOS in this study preferentially used the Internet for their information needs, as it had the advantages of convenience, privacy and accessibility, when compared with traditional mechanisms of information provision. Conclusion Giving a name to a collection of symptoms may bring relief and provide recognition that there really is a problem. However, with a diagnosis comes the need to have questions answered. A diagnosis of a chronic condition such as PCOS necessitates decision-making regarding possible treatment strategies and lifestyle choices. Information is needed in order to participate in shared decision making. The Internet proved to be a most versatile and beneficial source of information source for women with PCOS, if its limitations are taken into consideration.